1993
DOI: 10.1007/bf00025014
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of carbon and nitrogen as a function of the internal nitrogen status of a plant: Modelling allocation under non-steady-state situations

Abstract: In this paper we model allocation of carbon and nitrogen to roots and leaves as a function of the nitrogen status of a plant. Under steady-state conditions, allocation of carbon and nitrogen to leaves is exponentially (positively) correlated with plant nitrogen concentration, whereas allocation to roots is correlated negatively, also in an exponential manner.Allocation functions derived under steady-state conditions are used to simulate biomass partitioning under non-steady-state nutrient conditions. Upon nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Under these conditions plants are acclimated to a certain exponential addition rate of nitrogen and biomass partitioning as welt as rates of photosynthesis and respiration remain constant with time. Comparison of simulated and measured data indicated that these allocation functions obtained under steady-state conditions are also valid under non-steady-state situations (Van der Werf et al, 1993b). Later it will be shown that the allocation functions used in the model may be explained by the combined effect of cytokinins and sucrose on carbon and nitrogen allocation to shoots and roots in relation to nitrogen supply.…”
Section: Modelling Shoot and Root Growth In Relation To Nitrogen Supplymentioning
confidence: 80%
See 2 more Smart Citations
“…Under these conditions plants are acclimated to a certain exponential addition rate of nitrogen and biomass partitioning as welt as rates of photosynthesis and respiration remain constant with time. Comparison of simulated and measured data indicated that these allocation functions obtained under steady-state conditions are also valid under non-steady-state situations (Van der Werf et al, 1993b). Later it will be shown that the allocation functions used in the model may be explained by the combined effect of cytokinins and sucrose on carbon and nitrogen allocation to shoots and roots in relation to nitrogen supply.…”
Section: Modelling Shoot and Root Growth In Relation To Nitrogen Supplymentioning
confidence: 80%
“…Nitrogen is added at a low exponential rate of 0.0375 day-L For more detailed information on the description of the model, the reader is referred to Van der Weft et al (1993a,b). Allocation of daily assimilated carbon and nitrogen to shoots and roots is described as a function of the organic plant nitrogen concentration (Van der Werf et al, 1993b). These allocation functions were obtained for plants growing under steady-state conditions.…”
Section: Modelling Shoot and Root Growth In Relation To Nitrogen Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, conditions that decrease the specific activity of the shoot, such as a reduction in light intensity or CO 2 concentration, increase the dry-matter allocation toward the shoots (Wilson 1988;Enoch 1990). In some models root and shoot activity affect dry-matter allocation indirectly as the dry-matter distribution is related to the ratio of the C and N concentrations of the plant (Reynolds and Thornley 1982;Mäkelä 1986) or to the N concentration of the plant (Ågren and Ingestad 1987;Van der Werf et al 1993).…”
Section: Functional Equilibrium Modelsmentioning
confidence: 99%
“…Agren & Ingestad (1987) presented a similar argument, using a phenomenological model to understand root-shoot ratio in relation to plant-N status. Experimental data of Van Der Werf et a!. (1993a), De Pinheiro Henriques & Marcelis (2000 and De Groot et a!.…”
Section: Introductionmentioning
confidence: 99%